Colonial Australian Fiction Character Types, Social Formations and the Colonial Economy - Gelder, Ken (Sydney Studies in Australian Literature, 2017)
Over the course of the 19th century a remarkable array of types appeared in Australian literature: the swagman, the larrikin, the colonial detective, the bushranger, the currency lass", the squatter, and more. Some had a powerful influence on the colonies' developing sense of identity; others were more ephemeral. But all had a role to play in shaping and reflecting the social and economic circumstances of life in the colonies. In Colonial Australian Fiction: Character Types, Social Formations and the Colonial Economy, Ken Gelder and Rachael Weaver explore the genres in which these characters flourished: the squatter novel, the bushranger adventure, colonial detective stories, the swagman's yarn, the Australian girl's romance. Authors as diverse as Catherine Helen Spence, Rosa Praed, Henry Kingsley, Anthony Trollope, Henry Lawson, Miles Franklin, Barbara Baynton, Rolf Boldrewood, Mary Fortune and Marcus Clarke were fascinated by colonial character types.